SAT0330 Active Tuberculosis in Arthritis Patients Receiving TNF Inhibitors Despite Baseline Screening. (9th June 2015) - Soare, A.; Gherghe, A.M.; Dobrota, R.; Pintilie, S.; Oneata, R.; Ancuta, I.; Milicescu, M.; Martin, A.; Sasu, M.; Ciofu, C.; Macovei, L.; Stoica, V.; et al.
Abstract : Background: Screening for active and latent Tuberculosis (TB) is mandatory before TNF inhibitors (TNFi) initiation but despite all efforts made, TB still remains a major concern in these patients, especially in countries with a high TB burden. Objectives: To assess the incidence of active TB and the efficacy of TB prevention measures in a cohort of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) receiving TNF inhibitors, in a Romanian academic rheumatology center. Methods: Data of all patients who received treatment with TNFi in our clinic between 01.2001 and 01.2015 have been retrospectively analyzed. Demographic characteristics, baseline TB screening results, TB prophylaxis, exposure time to TNFi, and active TB cases were extracted from clinical records. Mandatory TB screening procedure at baseline included tuberculin skin test (TST) between 01.2001- 08.2010 (positive when >10 mm until 12.2004 and >5mm from 01.2005) and QuantiFERON®-TB Gold test (QTF) from 09.2010 to present. The cohort was divided into 3 groups, according to the TB screening method (TST1: 01.2001-12.2004, TST2: 01.2005-08.2010 and QTF: 09.2010-01.2015) and the frequency of active TB was analyzed. Latent TB reactivation (LTBR) was defined as TB occurring in the first 12 months of treatment. The influence of the screening method on active TB incidence was assessed using Cox proportional hazard regression. Results: 550 patients were included (305 RA, 42 PsA, 203 AS): 78 in TST1, 249 in TST2 and 223 in the QTF group. Baseline screening test was positive in 3.8% patients in TST1 group, 17.67% in TST2 group and 18.3% in QTF group. None of the patient receiving TB prophylaxis developed active TB. The number of active TB cases/time of exposure to TNFi in the 3 groups was 9/468.83, 9/1066.91 and 3/551.45 respectively, accounting for an incidence of 1919.67, 843.55 and 544.02 cases per 105 person years (PY). The incidence of TB in Romania, as reported to the World Health Organization, decreased from 147 to 94 per 105 PY from 2001 to 2012. Cases considered to be LTBR/total TB cases in TST1, TST2 and QTF groups were 2/9, 2/9 and 1/3 respectively, while the rest of them were appointed as new TB infection. Using Cox regression adjusted for age at TNFi initiation, sex, disease and treatment, we found no influence of the TB screening method on the risk of LTBR. However, the TST2 and QTF groups had a significantly lower TB risk, with the TST1 group as reference, when all cases of active TB were analyzed: HR [95% CI] were 0.19 [0.04-0.94], p=0.041 for TST2 and 0.09 [0.01-0.74], p=0.025 for QTF, suggesting that the period of TNFi initiation, when the TB incidence in general population was higher than in the later years, determined a higher risk for active TB. Conclusions: In a country with a high TB burden, where all arthritis patients started on TNFi were screened for latent TB, new TB infection exceeds LTBR. Baseline screening and prophylaxis was efficient in positive patients but it is not enough in preventing active TB on a long term and the screening protocol should be revised. Disclosure of Interest: None declared